Palavras e imagens que tecem histórias: ilustradores/escritores e a criação literária para a infância - Eliette Aparecida Aleixo (2014)
In this study, we investigate the process of producing childrens books, as written and illustrated by the same author, aiming to understand this dual authorship category. The questions asked in this study were the following: how do the illustration and writing of childrens books engage in a dialogue when they are written by the same author? Which authors represent this trend that becomes so frequent today throughout the literary production for children? What motivates illustrators of childrens literature to become writers? For this investigation, we provide a brief historical overview of childrens book illustration in a broader context so as to spotlight it in the Brazilian context later, focusing on illustrators, and illustrators/writers of books for childrens literature. The view on this subject is anchored in the assumptions of childrens literature scholars and childrens book illustration theorists. Through the representative samples of the Brazilian editorial production, according to the specificity observed, we contribute to the discussion of literature for children in Brazil grounded on a qualitative analysis. In order to achieve this goal, we have selected some contemporary illustrators/writers and examined some aspects related to the creative processes of these authors by means of the data obtained through interviews, cross-checked with the analysis of books featuring its creative process. In this analysis, we have considered the verbal and visual narratives, the graphic design, the cover, the arrangement of images and texts, the colours and the effects they produce, the page layout, among other elements that demonstrate the writers/illustrators style.